“Opening Innovation” Across Layers of Practices: Developing an Integrative View of the Emergence of Digital Health - Dionne, Karl-Emanuel; Carlile, Paul (Managing Inter-organizational Collaborations: Process Views, 2019)
Innovation challenges are increasingly complex, cutting across distributed actors from different disciplines, organizations, and fields. Solving such challenges requires creating the capacities of opening up for innovation to access and develop a greater amount and variety of knowledge and resources. Perspectives on open source, open innovation, and interorganizational collaboration have explored such capacities, but from different origins and scopes of analysis. Our practice-based integrative framework of “opening innovation” helps highlight these differences and connect their relative strengths. Through a critical literature review paired with an analysis of different empirical cases from Hacking Health, a non-profit organization helping drive digital health innovation, the authors reveal the user-centric, firm-centric, and field-centric approaches to opening innovation that progressively connect a greater variety of actors and resources. The authors show how specific new relational practices they produce address the new relational dynamics these connections bring to accumulate more resources for innovation to keep progressing.
Keywords: Collaboration interorganisationnelle; Healthcare; Innovation ouverte; Open source